EFEKTIVITAS TERAPI RELAKSASI NAFAS DALAM DAN AROMA TERAPI LEMON TERHADAP INTENSITAS NYERI DISMINORE PRIMER PADA REMAJA PUTRI KELAS VII DAN VIII DI SMP 1 BARUNA WATI TAHUN 2022 - Novitri, Ana Yulita; Herliana, Irma; Yuliza, Emi (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2023)
Biological changes occur during adolescence in females, marked by menstruation. Menstruation can cause pain in the abdominal and pelvic areas known as primary dysmenorrhea. However, the pain can be relieved through various methods, including deep breathing relaxation therapy and lemon aroma therapy. Therefore, this study aims to investigate the effect of deep breathing relaxation therapy and lemon aroma therapy in relieving pain during menstruation. This study is a Quasi-experimental research using the Two Group Pretest Posttest design with a total of 88 female students from grade VII and VIII at SMP Balrunal Walti Jakarta. Data collection technique uses a questionnaire that has been tested for validity. Data analysis in this study uses univariate and bivariate analysis to obtain the correlation or influence of deep breathing relaxation therapy and lemon aroma therapy on the intensity of primary dysmenorrhea in adolescent females. The results of the study, through the Wilcoxon Signed Rank Test, obtained a p-value of 0.000 which is less than the value of α = 0.05. It can be concluded that the use of lemon aroma therapy has an effect on the intensity of primary dysmenorrhea pain in female students of grade VII and VIII at SMP 1 Barunal Wati.